Organizing for collective feminist killjoy geographies in a US university. Issue 4 (3rd April 2021) - Al-Saleh, Danya; Noterman, Elsa
Abstract: Amid broader discussions of the continuities of racism and sexism on campuses in the United States, we bring together Sara Ahmed's notion of the 'feminist killjoy' with intersectional feminist geographers' focus on the politics of knowledge production to suggest that the academic department is a key site for anti-racist feminist intervention. Specifically, we survey our organizing experiences as members of Women in Geography (WIG) at UW-Madison, a long-standing group that supports female, non-binary, and gender-queer graduate students, faculty, and staff affiliated with geography. We argue that departmentally-situated groups such as WIG can cultivate anti-racist feminist praxis as collective feminist killjoys through diverse tactics that identify multiple points for intervention. In this paper, we focus on two specific tactics that WIG developed between 2016 and 2019, which include organizing feminist academic professional development activities and conducting a climate survey for geography graduate students. Critically reflecting on WIG's interventions in academic professionalization and climate, we find that a collective feminist killjoy orientation facilitates recognition of, and intervention in, shared - and differential - precarity.